Revisiting ab initio carcinoembryonic antigen and CA19-9 tumor markers in colorectal carcinoma in association with anatomotopographic location and staging of disease - Lerch, Milan; Sengul, Demet; Sengul, Ilker; Peteja, Matúš; Přibylová, Lenka; Gawel, Wladyslav; Pelikán, Anton; Tomaskova, Hana; Malý, Tomáš; Janout, Vladimír (Revista da Associação Médica Brasileira, 2023)
OBJECTIVE: This study purposed to evaluate preoperative two tumor markers, namely, carcinoembryonic antigen and carbohydrate antigen (CA)19-9, in colorectal cancer for anatomotopographic location with disease stage and to assess their utility for diagnostic staging purposes. METHODS: The study retrospectively incorporated patients who had undergone surgery for colorectal cancer at our department in 2015-2018 and in whom carcinoembryonic antigen and CA19-9 tumor markers had been preoperatively analyzed. The obtained data were then statistically processed using R-project. RESULTS: A total of 155 patients had been incorporated, of whom 96 (62%) were men and 59 (38%) were women. Rectum was the most common location (74 patients, 48%), and the least represented stage was IV (18, 12%). The marker carcinoembryonic antigen was obtained in all 155 cases, while CA19-9 was in 105. The median carcinoembryonic antigen was 3 (0.34-1104.25), and the median CA19-9 was 12 (0.18-840.00). A significance was recognized between median carcinoembryonic antigen and disease stage (p-value=0.016), with stages I, II, and III (medians 2, 3, and 2) different from stage IV (median 13), while no significance for CA19-9 was recognized (p-value=0.343). No significance between either marker and location (carcinoembryonic antigen: p=0.276; CA19-9: p=0.505) was detected. The testing was performed at a significance level of alpha=0.05. CONCLUSION: This study revealed a significance between the marker carcinoembryonic antigen, but not CA19-9, and the disease stage, while no relationship of either of these markers with tumor location was found. Herewith, the study confirmed that higher carcinoembryonic antigen values may suggest the finding of more advanced forms of colorectal cancer and thus a worse prognosis of this malignant phenomenon.
Keywords: Colorectal Neoplasms; karcinoembryonální antigen; CA-19-9 Antigen; mužské pohlaví; Retrospective Studies; lidé; Male; Carcinoembryonic Antigen; antigen CA-19-9; Biomarkers, Tumor; retrospektivní studie; ženské pohlaví; nádorové biomarkery; Female; Humans; kolorektální nádory